علاقة العدالة التنظيمية بسلوك المواطنة التنظيمية عند الأستاذ الجامعي دراسة ميدانية في كلية العلوم الاجتماعية والإنسانية بجامعة البليدة -2 - عـيـشــــــــوش, عـثـمـــــــــــــــــــــــــــان; دغمان, بوبكر الصديق (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى التعرف طبيعة العلاقة بين العدالة التنظيمية وسلوك المواطنة التنظيمية عند أساتذة كلية العلوم الاجتماعية والانسانية بجامعة البليدة -2-. حيث تكون مجتمع الدراسة من كل الأساتذة في الكلية، و تم اختيار عينة عشوائية بلغت 136 أستاذا من مجموع 192 استاذا في الكلية، و باستخدام المنهج الوصفي و المعالجات الاحصائية اللازمة من خلال برنامج SPSS V20 توصلت الدراسة الى: - عدم وجود فروق ذات دلالة احصائية في إدراك العدالة التنظيمية تعزى للجنس والسن، بينما هناك فروق تعزى للأقدمية والرتبة العلمية. - عدم وجود فروق في ممارسة سلوك المواطنة التنظيمية تعزى للجنس والسن والأقدمية والرتبة العلمية. - توجد علاقة ارتباطية ذات دلالة احصائية بين العدالة التنظيمية سلوك المواطنة التنظيمية عند أساتذة الكلية Stady empirical in faculty of human and social sciences at Blida-2- University This study aimed to identify the nature of the relationship between organizational justice and the behavior of organizational citizenship at the faculty of human and social sciences at Blida-2- University. Where the study community consists of all professors in the college, and was selected a random sample of 136 professors out of a total of 192 professors in the college, Using the descriptive approach and statistical treatments required through SPSS V20, the study concluded: - There are no statistically significant differences in the perception of organizational justice Attributed to gender and age, while there are differences due to seniority and scientific rank. - There are no differences in the practice of organizational citizenship behavior Attributed to gender, age, seniority and scientific rank. - There is a statistically significant relationship between organizational justice and organizational citizenship behavior
The relationship between organizational justice and the behavior of organizational citizenship in teacher’s university Stady empirical in faculty of human and social sciences at Blida-2- University
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: العدالة التنظيمية، المواطنة التنظيمية; justice organizational, organizational citizenship behavior.